Disrupted network architecture of the resting brain in attention‐deficit/hyperactivity disorder. Issue 9 (25th March 2014) - Sripada, Chandra; Kessler, Daniel; Fang, Yu; Welsh, Robert C.; Prem Kumar, Krishan; Angstadt, Michael
Abstract Background Attention‐deficit/hyperactivity disorder (ADHD) is one of the most prevalent psychiatric disorders of childhood. Neuroimaging investigations of ADHD have traditionally sought to detect localized abnormalities in discrete brain regions. Recent years, however, have seen the emergence of complementary lines of investigation into distributed connectivity disturbances in ADHD. Current models emphasize abnormal relationships between default network—involved in internally directed mentation and lapses of attention—and task positive networks, especially ventral attention network. However, studies that comprehensively investigate interrelationships between large‐scale networks in ADHD remain relatively rare. Methods Resting state functional magnetic resonance imaging scans were obtained from 757 participants at seven sites in the ADHD‐200 multisite sample. Functional connectomes were generated for each subject, and interrelationships between seven large‐scale brain networks were examined with network contingency analysis. Results ADHD brains exhibited altered resting state connectivity between default network and ventral attention network [P < 0.0001, false discovery rate (FDR)‐corrected], including prominent increased connectivity (more specifically, diminished anticorrelation) between posterior cingulate cortex in default network and right anterior insula and supplementary motor area in ventral attention network. There was distributed hypoconnectivity within default network (P = 0.009, FDR‐corrected), and this network also exhibited significant alterations in its interconnections with several other large‐scale networks. Additionally, there was pronounced right lateralization of aberrant default network connections. Conclusions Consistent with existing theoretical models, these results provide evidence that default network‐ventral attention network interconnections are a key locus of dysfunction in ADHD. Moreover, these findings contribute to growing evidence that distributed dysconnectivity within and between large‐scale networks is present in ADHD. Hum Brain Mapp 35:4693–4705, 2014. © 2014 Wiley Periodicals, Inc.